Sustainable food production practices in the Caribbean - Ganpat, W.G.; Isaac, W.A. (CTA / Ian Randle Publishers, 2012)
This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.This book’s expert authors have demonstrated that it is possible to increase agricultural yields in the Caribbean by more than 100 per cent in many cases through the simple application of sustainable practices. Here they demonstrate how. Applicable especially at the small-scale farmer level, the text addresses the issue of sustainable agriculture from a practical perspective. Although the scientific and technological aspects are given attention, the authors use their accumulated research and field experiences to focus on tested, simple production systems and practices that sustain soil fertility, ecosystems and people. Clearly written with practical guides and numerous illustrations, figures and tables, the 20 chapters of this book are organised as follows. The first three chapters are dedicated to soils and fertility, followed by sections on crop production and protection. The livestock chapters that come next are strongly based on the feed small ruminants use, including details on the cultivation of major feed resources. In addition, the potential of indigenous livestock and aquaculture are discussed. The book also addresses postharvest and quality assurance and marketing issues, closing with chapters on sustainable nutritional practices. The authors consistently advocate crop and livestock production techniques that require an agroecological approach. This approach aims at reducing the use of water, chemicals and pesticides and the preservation of the region’s soils.